Pengaruh Persepsi Keamanan dan Kepercayaan Konsumen terhadap Peningkatan Penggunaan E-Payment - Shalihah, Rana Mentari (Journal of Business Management Education (JBME), 2020)
Generally, many believe that the main factor in the development of electronic commerce is good security and trust. Security perceptions in the electronic payment system become a benchmark for consumers in electronic commerce transactions. This study aims to determine the effect of perceptions of security and consumer confidence on the increased use of electronic payment systems. The method used in this study is the type of library research (library research). Based on research that has been done, it can be concluded that the perception of security and consumer confidence both affect the increased use of electronic payment systems. The implication of this research is as a consideration for electronic payment system providers in their use by increasing the security and trust of consumers as a solution to overcome the problems of using electronic payment systems and increasing their use.